PENGANGKATAN PEJABAT STRUKTURAL DI LINGKUNGAN SEKRETARIAT DAERAH PROVINSI SUMATERA BARAT - , Zaki Fahminanda Rustam, SSTP, Dr. Ely Susanto, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Based on the phenomenon occurred in the appointment of structural officials at the regional secretariat of West Sumatra Province, it then conducted a research aimed to determine the implementation procedure of the structural appointments at regional secretariat of The Government of West Sumatra Province reviewed from the role of the institutions and the officials concerned. The implementation of structural appointments consist of several stages, ranging from personnel planning, job analysis, recruitment, selection and placement until the inauguration of the structural official. It is hoped to determine the problems existed in every stage, the role of implementing units and the role of individuals in the implementation of structural appointments. The research is used qualitative method. Primary data was obtained from informants of BKD, Bureau of the Organization, Baperjakat as well as structural echelon III and IV other officials agencies. Secondary data was analyzed from some relevant documents about appointment of structural official year 2009 to early 2011 gained from the Bureau of Organization and BKD. The implementation of the ideal and effective appointments for structural official was conducted gradually and systematically, from planning and analysis positions as an initial guidance appointment, followed with process of recruitment, selection and placement, and finally inauguration of the structural official. Based on results of the research, determined that appointment of the structural officials was implemented through the planning process, preparation of personnel formation, recruitment, competency tests, proposed candidates formation and then trial of Baperjakat without any analysis of ideal officials. The weakness of the data system is crucial in appointment of structural officials, whereby the recruitment of civil servants is still managed untransparently in each agency. Competency tests are also not very influential in the appointments of structural officials, because it is still questioned its transparency. Effectiveness of Regional Personnel Agency (Badan Kepegawaian Daerah ) as the Regional Planning and Development Office is still lack since in the implementation for appointment of structural officials, BKD had a role as a facilitator only. Governors as Trustees Regional Personnel officials have a very large role in the appointment of structural officials, especially the second echelon. Baperjakat only play a role in recommending of structural officials candidates to the Governor. Still, the decision was on the hands of the Governor. So it can be concluded that each phase of the appointment of structural officials is a long process in the implementation of personnel management. Because the decision appointments remain in the hands of the Governor. For further improvements, it is suggested to have a complete data base systems and computerized, the implementation of a more comprehensive analysis of position by forming a team that is given training on the analysis of position, changes in recruitment patterns as become more openly, the evaluation of any test of competence and its implementation to be more transparent , as well as making of regulations governing the appointment of structural officials.